REDESAIN PINTU MASUK PERPUSTAKAAN UNIVERSITAS SURABAYA - Melianita Kristianto Putri; Elieser Tarigan; Audit Yulardi (CALYPTRA, 2018)
Abstract -Library as a vehicle for lifelong learning, informative, research, and recreational to improve the intelligence and empowerment of the nation. Library in an educational world order serves to support the National Education System. The purpose of this paper is to design an entry access to support the improvement of the function of facilities in learning and research in library University of Surabaya. The learning method is qualitative method. Through the research, it is known what need is needed to redesign the library entrance. From the results of the study, will be designed the entrance of the library consisting of a desk monitor, access doors, and decorative cabinets. Which is where the entrance itself using fingerprint technology to facilitate the library of the University of Surabaya more easily obtain the data of library visitors both from within the environment and outside the environment of the University of Surabaya. So that the use of the entrance in the library University of Surabaya more optimal.